Aplikasi Teknologi Ramah Lingkungan dari Bahan Organik dan Anorganik untuk Material Tahan Gempa dengan Pendekatan Pembelajaran - Amir Mukhlis; Fita Nelyza; Ruslaini; Farah Ukhtia; Jaruzi Alberi (Akademi Farmasi YPPM Mandiri, 2023)
The problem of this community service is that the location of the partner activity is in a disaster-prone area so that the partner will be vulnerable to disaster. Apart from that, partners need to get support in the learning process. Partners also do not have adequate skills in learning approaches so this needs to be provided with a solution. The aim of this community service activity program is to provide partners with solutions to disasters through the use of environmentally friendly materials from organic and inorganic materials and provide a strengthening learning approach so that partners will be able to solve their problems with the science and technology that has been provided by program executor. For this reason, the solution provided is to provide knowledge about the application of environmentally friendly technology in the construction sector in the form of a mixture of organic concrete and inorganic concrete and provide an understanding of learning approaches. In this activity, building components are produced in the form of concrete floors derived from organic and inorganic waste, with several learning approaches.